In Vitro Propagation and Cellular Behaviour Studies of Severinia buxifolia (Poir.) Tenore - Hashimah, Elias; R.M., Taha; N.A., Hasbullah; N., Mohamed; S., Abdullah (ISHS, 2013)
In this study, a wild relative of Citrus, Severinia buxifolia, was subjected to tissue culture treatments in order to identify the best medium for plant regeneration of this species. This research was carried out due to its range of uses and because of its potential to be a rootstock species that is tolerant to boron. Different sources of explants were cultured on Murashige and Skoog (MS) media supplemented with various types and concentrations of hormones. Results indicated that responsive explants were from stems and cotyledons, based on the formation of shoots. The best shoot formation was observed on MS medium supplemented with 0.5 mg/L NAA and 1.0 mg/L BAP. The studies also included cellular parameters such as Mitotic Index (MI), chromosome counts, ploidy level determinationand nuclear DNA content, and mean cell and nuclear areas. Investigation of the changes that occurred as the plants were transferred from in vivo to in vitro conditions were also made. The results showed that the chromosome number in vitro was higher than in vivo. Besides, changes in MI, ploidy level or nuclear DNA content, mean cell and nuclear areas were detected which could lead to somaclonal variations.